Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability. Issue 1 (2nd January 2020) - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele
Abstract: Systems for instrumented motion analysis depend on an accurate biomechanical model. In this work an existing statistical shape fitting approach was adapted to register a parametrized human surface model with annotated anatomical landmarks to a point cloud obtained from one frontal depth camera view. Based on the obtained landmark positions joint centers, segment lengths and segment orientations of the lower body were calculated. The outcome was validated among two groups of healthy and impaired subjects, using a marker-based optical motion capture system. The results reveal a valid and reliable approach for obtaining an individualized lower body biomechanical model with minimum effort.